ANALISIS MANAJEMEN DANA DESA DALAM MENINGKATKAN PEMBANGUNAN DESA MENURUT PERSPEKTIF EKONOMI ISLAM (Studi Pada Desa Sungai Rambai Kecamatan Tebo Ulu Kabupaten Tebo) - Rio Iqlandia; M. Nazori; Mellya Embun Baining (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2023)
This study aims to determine the analysis of village fund management in improving village development according to an Islamic economic perspective. The results of the research conducted concluded that the village fund planning stage in Sungai Rambai Village was in accordance with what was planned by the village government, but there was a lack of participation by the Sungai Rambai village community in deliberations on determining the use of the village fund budget. In the view of Islamic economics, the government of Sungai Rambai village already has standard values of basic Islamic economics, namely being fair and responsible. The use of the Sungai Rambai village fund budget, Tebo Ulu sub-district, Tebo district can be seen from the successful financial performance of the village fund budget in 2017-2021 in the good category, all budget expenditures issued each year are in accordance with those realized.